PENGATURAN SAHAM PERUSAHAAN DALAM REZIM HUKUM INDONESIA DAN SINGAPURA SEBAGAI PEMBENTUKAN PASAR TUNGGAL ASEAN - Zulheri Zulheri (Universitas Airlangga, 2013)
Ideas to harmonize the regulation of ‘corporate shares’ (CS) in the corporate law of Indonesia and Singapore discussed in order to start up and embody the ASEAN Single Market. This article focused on different minimum standards and requirements (MS&R) in the transaction CS within two different corporate laws of Indonesia and Singapore. It is necessary to employ a conceptual approach, especially corporate share as a very basic of a company, to have a comparative legal analysis to reach a solution. Furthermore, it is to harmonize such standars and requirements on the CS transaction. It is necessary to use the theory of negative regional economic integration that significantly different with the conservative theory aplied inthe EU. As a result, the different regulation of CS between those two different company law regimes should be simplified by withdrawing their similiarities of MS&R. This may create an avenue to achieve the ASEAN’s single market in 2015. This new standar (model) would ease the process harmonization in which companies of ASEAN Countries can make a cross-ownership of CS by the mergers and acquisitions of transactions that timely make a strong position in the business competition regionally. I conclude that harmonization of MS&R of CS provided in company laws of Indonesia and Singapore would become a cornerstone for the ASEAN Single Market in which obstacle of joint market has been minimized or even abolished. However, harmonization of MS&R of CS should be in the corridor of sustainable global justice in the ASEAN market competition.Therefore, I recommend that both Indonesia and Singapore should develop a corporate culture in the spirit of the ASEAN Single Market, and review the regulation regarding company law of both countries, especially the CS and legal procedures of the cross-border mergers transaction and acquisition.